Functionalization of nano-emulsions with an amino-silica shell at the oil–water interface1. Issue 91 (9th October 2015) - Attia, Mohamed F.; Anton, Nicolas; Bouchaala, Redouane; Didier, Pascal; Arntz, Youri; Messaddeq, Nadia; Klymchenko, Andrey S.; Mély, Yves; Vandamme, Thierry F.
<x xml:space="preserve">Abstract</x> A new and simple method of modify and functionalize the liquid/liquid interface of nano-emulsion droplets.